All Days 2016
DOI: 10.2118/179907-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Stability of Scale Inhibitors and its Impact on Processing Plants

Abstract: Petroleum, which is one of the most complex mixtures existing in nature, is equilibrated and coexists with the aqueous phase at reservoir conditions. However, depending on the oil viscosity, strong emulsions may be formed due to the high shear imposed by the production process. As a consequence higher temperatures conditions are necessary for the oil separation treatment. Therefore it is important to assure that scale inhibitors are thermally stable and able to act in what are considered extreme temperatures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In contrast to DETPMP, the thermally aged PVS exhibited no degradation and remained above the effective minimum concentration of 5 mg/L PVS for barite in all tested assays. 18 Sorbie and Laing concluded that nucleation inhibition was the primary mechanism that prevented scale formation with PVS and reported a MIC of 1 mg/L PVS for mixed brines containing synthetic seawater and Brent formation water. 19 Graham et al investigated the effects of pH and other experimental variables (e.g., flow rate, run time, prescaling, and mixed scale) on MIC values for PVS and reported MICs of ∼1 mg/L at pH 2.4 and 6.0 in a 50:50 mixed Mungo formation water/seawater, 1.25−5 mg/L for low-barium sulfate scaling brine systems, and 0.25−2 mg/L for low-carbonate scaling brine systems.…”
Section: ■ Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast to DETPMP, the thermally aged PVS exhibited no degradation and remained above the effective minimum concentration of 5 mg/L PVS for barite in all tested assays. 18 Sorbie and Laing concluded that nucleation inhibition was the primary mechanism that prevented scale formation with PVS and reported a MIC of 1 mg/L PVS for mixed brines containing synthetic seawater and Brent formation water. 19 Graham et al investigated the effects of pH and other experimental variables (e.g., flow rate, run time, prescaling, and mixed scale) on MIC values for PVS and reported MICs of ∼1 mg/L at pH 2.4 and 6.0 in a 50:50 mixed Mungo formation water/seawater, 1.25−5 mg/L for low-barium sulfate scaling brine systems, and 0.25−2 mg/L for low-carbonate scaling brine systems.…”
Section: ■ Introductionmentioning
confidence: 73%
“…Additionally, phosphate-based SIs raise environmental concerns due to large amounts of phosphorous introduced into the environment . Organic polymers such as poly­(vinyl sulfonic acid) (PVS) can tolerate high temperatures, and many studies have proven their effectiveness for barite scale at low concentrations. For example, Rosa et al investigated the performance of several barite SIs, including DETPMP and PVS, at temperatures between 60 and 160 °C. In contrast to DETPMP, the thermally aged PVS exhibited no degradation and remained above the effective minimum concentration of 5 mg/L PVS for barite in all tested assays .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each cell was filled with a synthetic brine solution in deionized water, composed of 33 g/L NaCl, 7.360 g/L NaHCO 3 , and 2.843 g/L Na 2 SO 4. [38][39][40] Once the tests would be carried out for a long time, the cells remained at room temperature and under mechanical agitation to maintain the physicochemical properties of the brine solution throughout the experiments. All electrochemical results were acquired with the help of a Potentiostat/Galvanostat AUTOLAB PGSTAT302N.…”
Section: Electrochemical Testsmentioning
confidence: 99%
“…In this context, the knowledge of the concentration of dissociated salts in the aqueous phase at different conditions of supersaturation, pH, temperature, and pressure allows for the monitoring of the nucleation phenomena and crystal growth kinetics of these salts. The nucleation, precipitation, and growth of inorganic crystals responsible for the incrustation can be avoided/delayed using data associated with salt precipitation rates in the presence of chemicals scale inhibitors (Antony et al., 2011; Fan et al., 2009; Rosa et al., 2016). Besides the efficiency of the scale inhibitors used, the understanding of their action mechanisms is essential to reduce environmental impacts resulting from their incorrect disposal and also to minimize cost (Reis et al., 2011).…”
Section: Introductionmentioning
confidence: 99%